The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1017/s1481803500003493
|View full text |Cite
|
Sign up to set email alerts
|

Radiation doses to emergency department patients undergoing computed tomography

Abstract: Objectives: Computed tomography (CT) use is increasing in the emergency department (ED). Many physicians are concerned about exposing patients to radiation from CT scanning, but estimates of radiation doses vary. This study's objective was to determine the radiation doses from CT scanning for common indications in a Canadian ED using modern multidetector CT scanners. Methods: We conducted a health records review of consecutive adult patients seen at two busy tertiary care EDs over a 2-month period who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…The estimated radiation doses of all performed CT examinations in this study were below national diagnostic reference levels. Worall et al reported radiation doses for 2720 emergency department patients undergoing CT (26). In comparison, the median estimated radiation doses in our study were almost equal for cranial CT (2.6 versus.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The estimated radiation doses of all performed CT examinations in this study were below national diagnostic reference levels. Worall et al reported radiation doses for 2720 emergency department patients undergoing CT (26). In comparison, the median estimated radiation doses in our study were almost equal for cranial CT (2.6 versus.…”
Section: Discussioncontrasting
confidence: 53%
“…Worall et al. reported radiation doses for 2720 emergency department patients undergoing CT (26). In comparison, the median estimated radiation doses in our study were almost equal for cranial CT (2.6 versus.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary embolism (PE) can be life-threatening and, when suspected, is usually investigated by computed tomographic pulmonary angiogram (CTPA). Concerns related to overutilization and harmful ionizing radiation have identified CTPA as an area in need of resource stewardship . The purpose of this study was to explore interphysician variability in CTPA diagnostic yield and to identify any associated physician characteristics that could inform an intervention to reduce overuse in our institution.…”
mentioning
confidence: 99%
“…Mean doses of radiation from a simple CT head could range between 2 and 2.9 millisieverts (mSv). 14,15 Though the exact magnitude of risk is controversial at lower doses, the cumulative dose of multiple studies may potentially expose patients to the side effects of radiation.…”
Section: Ct Scan and Mrimentioning
confidence: 99%